2004
DOI: 10.1177/0193723504267546
|View full text |Cite
|
Sign up to set email alerts
|

The Next M. J. or the Next O. J.? Kobe Bryant, Race, and the Absurdity of Colorblind Rhetoric

Abstract: In this essay, the author explores the absurdity of colorblind rhetoric within the discursive field of Kobe Bryant's rape trial. Specifically, in examining articulations on the Internet, television coverage, commentaries, and news reports, this article reveals how colorblind ideologies that dominate public discussions conflict with the racialized discursive utterances surrounding Kobe's arrest and ongoing trial. In exploring the reactions to accusations of rape against Kobe Bryant by both the mainstream media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 9 publications
0
58
0
Order By: Relevance
“…This article has demonstrated that color-blind ideology is so entrenched and pervasive in contemporary Western sport (Leonard, 2004) that its (re)production is not exclusively the preserve of white groups. In fact, it has the capacity to compel minority ethnic participants at times to endorse dominant claims that the effects of racism are overstated as well.…”
Section: Discussionmentioning
confidence: 98%
“…This article has demonstrated that color-blind ideology is so entrenched and pervasive in contemporary Western sport (Leonard, 2004) that its (re)production is not exclusively the preserve of white groups. In fact, it has the capacity to compel minority ethnic participants at times to endorse dominant claims that the effects of racism are overstated as well.…”
Section: Discussionmentioning
confidence: 98%
“…Ferber (2007), like Leonard (2004), is perplexed by the contradictions she sees in the way blackness is adored on the track, while white supremacy and racism continue unabated in wider society. Though colour-blindness is an ideal state to achieve, its practice is problematic.…”
Section: Political Race Consciousness: Challenging 'Race' Talkmentioning
confidence: 99%
“…Leonard (2004) argues that sport and PE are used as strategies to maintain white privilege as colour-blindness is supposedly affirmed through the symbolic representation of 'race' within. Critical race theorists argue that we live in a society structured by 'race' and racism, and that consequently we do not live in a 'race' neutral meritocracy (Gillborn 2008;Hylton 2005Hylton , 2009Solórzano and Yosso 2002).…”
Section: Political Race Consciousness: Challenging 'Race' Talkmentioning
confidence: 99%
“…In both cases he is a creature of the environments he inhabits. Mills (1997, 42) Stiviano's femininity which forces him to reinscribe/re-mark and subjugate Black bodies while re-establishing White supremacy in his sport (Leonard 2004). As such, Sterling speaks to her as a confidant/mentor would their philosophies, about how he perceives the world to be and how best to navigate a "culture" he is unwilling to use his influence to change.…”
Section: Backstage Racism and Frontstage Defencementioning
confidence: 99%